Studies on the inheritance of milking capacity in dairy cattle - Robison, O. J. (The University of Edinburgh, 1931)
From the analyses of these data, the mode of inheritance of butter -fat yield appears to be purely autosomal, whilst that of milking capacity appears to be affected by sex -linked factors. But consideration must be taken of the fact that unfortunately these data do not constitute a purely random sample of all cows in a herd and the elimination of low yielding cows ay cloud the results to some extent more especially as the Ayrshire breed has been selected to a greater extent for milk production than for butter fat Making allowances, however, for this fact and also the effect of environment etc., the great difference in the measures of variation between the milk yields of the two sets of granddaughters (paternal and maternal grandsiresj is significant. This significance is supported by similarity of this..same measure in the case of butter-fat yields. These results point towards the possibility of the inheritance of Milking capacity being sex-linked from the analyses of these data, it is impossible to say that part of the milking capacity of an animal is affected in this way as it may be the maximum yield or persistency of the lactation or, again it may only affect cows above or below a certain yield. Should this theory of sex-linkage be proved, it will be of great value to the breeder and improver of livestock, as it will give at least one definite course to follow in breeding practices. Great value would.lie in the facilitation of the choice of stock for the purposes of introduction of new blood lines into a herd. Especially in a dairy herd, the purchase of a new sire is a serious question as an unfortunate choice can .do great harm which tames year to obliterate. At present, the choice of selection of the bull is influenced largely by the quality of his sire or brothers and of secondary importance, his dam. A great number of untested bulls depend for their value upon their sires. Should any of the factors for milking capacity be sex-linked, then the value of the bull's sire in so far as his transmitting powers of characters for milking capacity are concerned will be greatly decreased. Attention regarding milking qualities will then have to be directed more towards the bull's dam and her parents, rather than to his sire. Until further investigations have been made more definite proof cannot be found to support the theory of sex linkage. Such proof would be abundantly found in systematic development of progeny tests. Less emphasis should be laid upon the sire of the bull and his pedigree but of utmost value is the quality of his offspring as an indication of his powers of transmission. In judging the quality of offspring, the quality of the dam must be taken into consideration. A sire used in a herd of low milk rec:rd average can easily raise the herd average to quite a large extent without himself being of much value. The valuable sire is one who, either maintains, or raises his daughters' average above those of high yielding dams. Pedigree alone is no indication of transmitting ability as some purebred sires are not even good enough for use in scrub herds. Great advancement has been made in Denmark along these lines and all herd sires used must have previously passed the progeny test. Faber (38,39) states that the Danish Government will not allow a bull to be eligible for a Government prize unless his daughters': records, as well as his pedigree, can be shown. Also some cattle breeding societies note the yield of the dam, sire's dam and dam's dam of bulls bought by them. Wriedt advises the publication of a list of bulls suitable for use as herd sires. The sons of these bulls should be selected by genotype regarding the performance of sire and dam and finally sire's dam. Lastly selection should be influenced by the exterior when the most important economic characters should be considered. In this country, apart from an occasional progeny class at an agricultural show, very little attempt at improvement has been made in this direction. Milk recorded cows which reach a certain standard can become qualified bull breeders but no emphasis is laid upon the necessity of using bulls from such dams as herd sires. Granted, their market value may be higher but the vital importance of using such sires is not sufficiently recognised. Bulls considered unfit for breeding purposes in Ireland are imported into this country, where, presumably they finally become herd sires. A glance through the literature dealing with the improvement dairy stock in America through the use of purebred tested sires shows what can be accomplished by practising rigorous systematic selection and breeding. SUMMARY OF RESULTS OF ORIGINAL INVESTIGATION: 1. Material consisting of the milk and butter fat yields of over 50,000 pairs of Ayrshire cows is used in the study of the mode of inheritance of milking capacity. 2. Correction factors are applied to age of animals and selection of data eliminated effect of environment length of lactation, etc. 3. Butter-fat yield analyses results indicate that as the degree of relationship increases, the measure of variation between these yields also increases. 4. Milk yield analyses suggest the occurrence of sex-linkage in the inheritance of milking capacity. The measures of difference in groups where the common inheritance of sex linked factors is possible, is smaller than in groups where such is rat possible. 5. Examination of number of pairs in each class indicates that breeders select their stock according to the male ancestry rather than the female.